Unveiling the Impact of Design Methods on Problem-Solving Performance in Undergraduate Stem Education - Torres-Benoni, F (OmniaScience, 2024)
Problem-solving is at the core of engineering design, being fundamental for systematic innovation. During their education, students are taught numerous methods and tools, despite that literature shows debatable results regarding their real impact. Consequently, this study aims to quantify the relative impact of design methods on undergraduate students’ problem-solving performance and determine if this influence goes beyond their background and the problem’s complexity. Utilising novelty, variety, and quality as criteria, the work done by 144 students was evaluated, solving two problems using three methods. The results show a performance improvement of up to 46% when working with methods that guide solution development through design principles. The context and the student method preference did not affect their performance, while the increment in the problem’s difficulty improved novelty and variety (15% and 11%) but reduced quality (34%). Surprisingly, the best-performance method was the least preferred, indicating the need of exploring the relationship between performance and actual use. The study results validate the work invested in teaching design methods, indicating the characteristics of the most efficient ones, beyond expert opinion. The structure of the study allows replication and could help future comparison of results. © (2024), (OmniaScience). All rights reserved.